(untitled) (Herald of the National Children’s Medical Center, 2025)
Liver resections are among the most complex and traumatic operations in abdominal surgery, especially in pediatric practice. The liver area is highly innervated and is associated with an increased risk of blood loss, which requires maximum anesthetic control. Adequate anesthetic management plays a key role in reducing mortality, minimizing blood loss, and improving treatment outcomes.